Corporate bonds and structured financial products - Choudhry, Moorad (Fixed income markets library.)
This book is a detailed account of the instruments that are used in the corporate bond markets, from conventional "plain vanilla" bonds to hybrid instruments and structured products. There is background information on bond pricing and yield, as well as a detailed look at the yield curve. The book covers the full set of instruments used by companies to raise finance, and which are aimed at a wide range of investors. It also discusses the analysis of these instruments. Topics covered include: *Bond basics *The yield curve *Callable bonds *Convertible bonds *Eurobonds *Warrants *Commercial paper *Corporate bonds credit analysis *Securitisation *Asset-backed securities *Mortgage-backed securities *Collateralised Debt Obligations *Synthetic CDOs Written by one of the leading names in the fixed income markets today, this book should prove to be an invaluable reference guide for all those with an interest in corporate bond markets, whether as practitioners, consultants or researchers. * Covers every major aspect of corporate credit markets * Features bond instruments as well as aspects of bond analysis * Covers conventional bonds as well as securitisation and structured financial products.